Internet Tiered Services Theory, Economics, and Quality of Service - Rouskas, George N. (Springer US : Imprint: Springer, 2009)
Internet Tiered Services: Theory, Economics, and Quality of Service (QoS) presents a theoretical framework for reasoning about and pricing Internet tiered services, and develops a practical algorithmic toolset for network providers to develop customized menus of service offerings. The material includes a comprehensive study of the design, sizing, and pricing of tiered structures for Internet services, and illustrates their potential in simplifying the operation of complex components such as packet schedulers. Specifically, the book addresses the following issues: Optimization of service tier selection and sizing, using fundamental concepts from location theory; several variants of the problem are considered, including deterministic vs. stochastic demands. Economic models for optimal pricing of service tiers that take into account simultaneously the (usually conflicting) objectives of users and providers. Models for optimizing "bundles of services," e.g., when a provider offers a service that includes both access bandwidth and data storage. Applications of tiered services in simplifying important QoS functions in the network, including fair packet scheduling. Internet Tiered Services: Theory, Economics, and Quality of Service is a useful resource for engineers in the fields of Internet services, economics, and quality of service (QoS) in network resource allocation.